Evaluation of Titiwangsa Lake water quality for an alternative sources of water supply - Sofea Natasha, Shaharudin (2018)
The purposes of the study was to determine the current water quality status of the Titiwangsa Lake and to obtain classification of the water at the lake based on National Water Quality Standard (NWQS) and Water Quality Index (WQI). Station 1 and station 2 were the two station that were selected for the sampling purposes. Total of sixteen (16) parameter were analyzed based on ex-situ test (conduct at the laboratory) and insitu test (conduct at the sampling site) where the sample were collected on February and April. In-situ test including temperature, pH, turbidity, and dissolved Oxygen (DO) while ex–situ test including Total Suspended Solid (TSS), Chemical Oxygen Demand (COD), Biochemical Oxygen Demand (BOD), Ammoniacal Nitrogen, Nitrate, Phosphorus, Total Coliform Bacteria, Escherichia Coli (E.coli) and Heavy Metal such as Cadmium (Cd), Copper (Cu), Zinc (Zn), and Lead (Pb). Based on the analysis and test that being done, Titiwangsa Lake was classified as Class IIB which is suitable for recreational use and suitable for body contact based on Water Quality Index (WQI) that being calculated. However, there are many activities that being conducted around Titiwangsa Lake such as water sport (kayak), recreational activities (picnic), algae growth in the lake and the food court area around Titiwangsa Lake may contribute to the pollution of the lake. Best action must be taken in order to protect the lake from being polluted due to these activities.